The effect of theophylline-ethylenediamine in Cheyne-Stokes respiration - Marais, O. A. S. (The University of Edinburgh, 1945)
Localisation of the respiratory centre:- The respiratory centre, which is constituted by the integration of many neurons, has been localised . in e relatively extensive area between the upper border of the pons and the lower third or so of the medulla oblongata. It has been demonstrated by V. E. Henderson and Craigie, by Gesell, Bricker and Magee that these neurons are scattered at different levels through the formatio reticularis of the se parts of the brain stern. The centre is bilateral and each half contains inspiratory and expiratory components that control muscles of inspiration and expiration respectively.

The nervous structures controlling respiration has been localised by Markwald. The fact that powerful and prolonged tonic inspiratory movements supervened after bilateral section of the vagus nerves and division of the brain stem immediately behind the posterior colliculi, made him conclude that a centre inhibitory to respiration was located in the posterior colliculi.

Tine vagi however also has an inhibitory action, consequently these inspiratory movements, or "cramps", as he termed them, appeared only after their influence had been abolished as well. In recent years Lumsden found that prolonged inspiratory movements occurred only if the section passed through the pons e few millimetres behind its anterior border, and occurred whether the vági were divided or not, and . that these respiratory movements were dependent upon an apneustic or inspiratory centre situated at the level of the striae accousticae, which was dominated normally by an inhibitory or pneumotoxic centre situated 'i.n the upper part of the pons. On account of the inhibitory influence of the latter, the apneustic n-ovements were transformed into the rhythmical movements characteristic of normal respiration, as shown by the fact that rythmic action currents are registered by leads from the medulla. Section of the brain stem behind the atriae accousticae brought about a series of gasps occurring at relatively long intervals.